2015
DOI: 10.1016/j.jas.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of early islanders in the Philippines during the Terminal Pleistocene/Early Holocene boundary: pXRF-analysis of obsidian artefacts

Abstract: This study analysed over 1000 obsidian stone artefacts excavated from two adjoining shelters on Alor Island Indonesia using portable XRF. The study showed an unambiguous separation of three different source locations (Groups 1, 2 and 3). Two sources (Group 2 and 3a, b, c) dominate the assemblage numerically. Group 1 and 2 indicate use of a single volcanic formation with a strong match between Group 1 artefacts and artefacts from sites in Timor Leste. Obsidian occurs in the earliest occupation layer in the Alor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…Recent research has shown that social interaction between distant communities, including maritime transportation of raw materials in ISEA, can be traced back to the terminal Pleistocene -early Holocene and it has been proposed that these changes might be associated with sea-level rise in post-LGM times (Bulbeck, 2008, Neri, et al, 2015, Torrence and Swadling, 2008. Sea-levels during the Pleistocene/Holocene boundary at 11,000 -12,000 cal BP rose on average 12 m kyr -1 (Grant, et al, 2012) and it has been argued that the loss of landmass from rising seas would have put established populations under pressure to adapt a more coastal and maritime focused economy Richards, 2013, Soares, et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has shown that social interaction between distant communities, including maritime transportation of raw materials in ISEA, can be traced back to the terminal Pleistocene -early Holocene and it has been proposed that these changes might be associated with sea-level rise in post-LGM times (Bulbeck, 2008, Neri, et al, 2015, Torrence and Swadling, 2008. Sea-levels during the Pleistocene/Holocene boundary at 11,000 -12,000 cal BP rose on average 12 m kyr -1 (Grant, et al, 2012) and it has been argued that the loss of landmass from rising seas would have put established populations under pressure to adapt a more coastal and maritime focused economy Richards, 2013, Soares, et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Until recently it has been assumed that seafaring technology during the Pleistocene and Early Holocene was simple and maritime interaction networks limited. In ISEA the assessment of maritime capability has changed in the last decade with evidence showing Upper Pleistocene hunter-gatherers ability for pelagic fishing (O'Connor, et al, 2011), increased social interaction between distant communities, including maritime transportation of raw materials being traced back to the terminal Pleistocene -early Holocene transition (Bulbeck, 2008, Neri, et al, 2015, Torrence and Swadling, 2008, and indications that a 'community of practice' existed in pre-Neolithic societies connecting islands in shared 'identities ' (O'Connor, et al, forthcoming).…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to what happened in the past, the pursuit for more efficient and more precise sourcing techniques (see e.g. Frahm and Feinberg, 2013;Kudriavtsev et al, 2015;Yi and Jwa, 2016), the reassessment of 'older' methods (Frahm, 2012a), or even the multiplication of pXRF applications across the world (Craig et al, 2007;Jia et al, 2010;Burley et al, 2011;Sheppard et al, 2011;Milić, 2014, Neri et al, 2015 are not conducted self-sufficiently anymore, e.g. for the only purpose of method development.…”
Section: Discussionmentioning
confidence: 99%
“…Mansiri's location is unexplained at this stage, but would fit with the hypothesis that agricultural expansion followed an opportunistic pattern whereby arable land along large freshwater systems provided the primary targets for farming communities after an initial maritime spread of people and innovations (Bellwood 2005). On the other hand, recent research has shown that social interaction between distant communities, including maritime transportation of raw materials in ISEA, can be traced back into the early Holocene period and might be associated with sea-level changes following the Late Glacial Maximum (Torrence and Swadling 2008;Neri et al 2015;Pawlik et al 2015). Considering the intensification of forest management evidenced at Niah Cave in Sabah (Barker et al 2011) and early independent domestication of tuber crops in highland Papua New Guinea (Denham et al 2003), it seems that the transition to pottery production and agricultural systems in ISEA was indeed complex and most likely a process that involved multiple migrations (Tumonggor et al 2013), as well as staggered acceptance and discard of innovations by local communities over hundreds of years.…”
Section: Discussionmentioning
confidence: 99%